2015
DOI: 10.1161/jaha.115.001859
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oximetry as a Real‐Time Monitoring Tool to Assess Quality of In‐Hospital Cardiopulmonary Resuscitation and Post Cardiac Arrest Care

Abstract: BackgroundRegional cerebral oxygen saturation (rSO2) as assessed by near infrared frontal cerebral spectroscopy decreases in circulatory arrest and increases with high-quality cardiopulmonary resuscitation. We hypothesized that higher rSO2 during cardiopulmonary resuscitation and after return of spontaneous circulation (ROSC) would predict survival to discharge and neurological recovery.Methods and ResultsThis prospective case series included patients experiencing in-hospital cardiac arrest. Cerebral oximetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Ibrahim et al [41] in hospital study documented that there was a significant difference in rSO 2 between survivors compared with those who died at initiation of resuscitation (35 vs. 17.5%, P ¼ 0.03) and during resuscitation (36 vs. 15%, P ¼ 0.0008). Ibrahim et al did not find any difference in rSO 2 between survivors and nonsurvivors regarding ROSC or post arrest period values, and no association between cerebral performance category score and rSO 2 at ROSC, during resuscitation, or post arrest.…”
Section: Post Restoration Of Spontaneous Circulationmentioning
confidence: 93%
“…Ibrahim et al [41] in hospital study documented that there was a significant difference in rSO 2 between survivors compared with those who died at initiation of resuscitation (35 vs. 17.5%, P ¼ 0.03) and during resuscitation (36 vs. 15%, P ¼ 0.0008). Ibrahim et al did not find any difference in rSO 2 between survivors and nonsurvivors regarding ROSC or post arrest period values, and no association between cerebral performance category score and rSO 2 at ROSC, during resuscitation, or post arrest.…”
Section: Post Restoration Of Spontaneous Circulationmentioning
confidence: 93%
“…In these studies of PCAS patients in the intensive care unit (ICU), rSO 2 was significantly lower in nonsurviving (Meex et al, 2013;Ahn et al, 2014) and poor neurological outcome patients (Storm et al, 2014) than in surviving or good neurological outcome patients. In contrast, Ibrahim et al (2015) reported that there was no difference between the rSO 2 of survivors and nonsurvivors in the ICU setting. Recently, Ihara et al (2019) showed that there was no difference in the rSO 2 value between severely brain-injured PCAS patients with abnormal amplitude-integrated electroencephalography (aEEG) and mildly brain-injured patients with continuous aEEG wave.…”
Section: Introductionmentioning
confidence: 94%
“…I n several studies, near-infrared spectroscopy (NIRS) has been used to measure regional cerebral oxygen saturation (rSO 2 ) in patients with postcardiac arrest syndrome (PCAS) to predict the outcome and analyze the brain's metabolic status (Meex et al, 2013;Ahn et al, 2014;Storm et al, 2014;Ibrahim et al, 2015). In these studies of PCAS patients in the intensive care unit (ICU), rSO 2 was significantly lower in nonsurviving (Meex et al, 2013;Ahn et al, 2014) and poor neurological outcome patients (Storm et al, 2014) than in surviving or good neurological outcome patients.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Ibrahim et al in this issue of JAHA describes how cerebral oximetry measured during cardiopulmonary resuscitation (CPR) is associated with restoration of pulses and survival . The authors consider whether this technology, which is portable, noninvasive, and easy to apply, could be used to guide resuscitation.…”
Section: Introductionmentioning
confidence: 99%